Global imaging of polar cap patches with dual airglow imagers. Issue 1 (14th January 2014) - Hosokawa, K.; Taguchi, S.; Shiokawa, K.; Otsuka, Y.; Ogawa, Y.; Nicolls, M.
<x xml:space="preserve">Abstract</x> During a 2 h interval from 2240 to 2440 UT on 12 November 2012, regions of increased 630.0 nm airglow emissions were simultaneously detected by dual all‐sky imagers in the polar cap, one at Longyearbyen, Norway (78.1°N, 15.5°E) and the other at Resolute Bay, Canada (74.7°N, 265.1°E). The Resolute Bay incoherent scatter radar observed clear enhancements of the F region electron density up to 1012 m−3 within these airglow structures which indicates that these are optical manifestations of polar cap patches propagating across the polar cap. During this interval of simultaneous airglow imaging, the nightside/dawnside (dayside/duskside) half of the patches was captured by the imager at Longyearbyen (Resolute Bay). This unique situation enabled us to estimate the dawn‐dusk extent of the patches to be around 1500 km, which was at least 60–70% of the width of the antisunward plasma stream seen in the Super Dual Auroral Radar Network convection maps. In contrast to the large extent in the dawn‐dusk direction, the noon‐midnight thickness of each patch was less than 500 km. These observations demonstrate that there exists a class of patches showing cigar‐shaped structures. Such patches could be produced in a wide range of local time on the dayside nearly simultaneously and spread across many hours of local time soon after their generation.